A Recipe for What? UK Universities, Enterprise and Knowledge Transfer - David Pickernell (The International Journal of Entrepreneurship and Innovation, 2010)
Universities play multiple knowledge-related roles in economies, creating (or co-creating), absorbing, disseminating and utilizing knowledge. These roles, however, are not without difficulty, for reasons related to universities themselves and the small firms that need to use such knowledge. This paper uses the UK Federation of Small Businesses 2008 survey to examine (a) the mechanisms in place to facilitate the dissemination to small and medium-sized enterprises (SMEs) of university knowledge and assistance; (b) the relative importance of the contribution of university-derived assistance to SMEs; (c) the relationship between the assistance obtained from universities and the requirements and capabilities of SMEs; and (d) the relationships between university-derived assistance and measures of growth.